The Ghost in the Machine: Gilliam's Postmodern Response in Brazil to the Orwellian Dystopia of Nineteen Eighty-Four. - Erickson, John (Utopian Studies, 1993)
Compares the concept of dystopia found in the book `Nineteen Eighty-Four,' by George Orwell with the idea presented in the motion picture `Brazil,' directed by Terry Gilliam. Scenes from both the book and the motion picture; How the book and the film treated totalitarian state; Discussions on the characters of both works.